Keanekaragaman Struktur Reproduksi pada Tumbuhan Paku Epifit di Kawasan Kampus IPB, Dramaga, Bogor: Diversity of Reproductive Structure in Epiphytic Ferns in the Campus Area of IPB University, Dramaga, Bogor - Badriah, Siti Nurul; Chikmawati, Tatik; Ratna Djuita, Nina (Jurnal Sumberdaya Hayati, 2025)
IPB University is a campus with high biodiversity and a well-maintained ecosystem. Many plants species have been found including epiphytic ferns, which are particularly abundant. However, information for their reproductive structure remains limited. This study aims to characterize the reproductive structure of epiphytic ferns growing in the IPB University campus area, Dramaga, Bogor. The sorus was collected from the epiphytic ferns and preserved using 70% alcohol. Epiphytic fern spores were observed using a compound microscope connected to an optilab camera. Fern spore measurements were carried out using the ImageRaster v2.1 application. The observed epiphytic ferns varied in the arrangement and location of the sorus and the characteristics of the spores. A total of 22 types of ferns have monolete spore forms with laesura lines, one type of spherical shape, and one type of tetrahedral-globose form with triradiate laesura. Spore sizes found were medium, large, and very large. All spores had a P/E ratio value of ≤1.00 with peroblate, oblate, suboblate, round oblate, and round prolate types. The surface of the perispora is very diverse, including alate-angular, globules, shallow verrucae, verrucate, echinulate, tuberculate, rugate, globules, echinate, laevate, cristate, regulate, colliculate, granulose, and costate-alate.